Causality and storytelling - Domsa, Zsófia; Horváth, Márta; Szabó, Judit (nCOGNITO - Kognitív Kultúraelméleti Közlemények, 2023)
The papers in this issue of our journal extend the exploration of the role of causality in understanding stories initiated in the previous issue, drawing on recent research in cognitive science. They conceptualize causality as a mental construct used to establish a causal relationship between two or more factors. The papers investigate how different genres, story types, and narrative styles engage causal thinking processes in collaboration with other mechanisms that shape artistic composition. The contributions in our journal employ various approaches to examine the significance of causal cognition, with most papers in this volume addressing the specific challenges of causality from the perspective of a selected theoretical construct.